Modular Equipment for Implementation of Power Electronic Topologies - Garrido, Daniel Oscar (2020)
This article presents a modular equipment thatallows the implementation of single-phase or three-phase powerelectronics topologies for research applications. The designedequipment includes an interface to adaptation of signals thatis compatible with Digital Signal Controllers (DSC) modelsTMS320F28377D and TMS320F28335. In addition, drivers compatiblewith uni-directional or bi-directional power devices weredesigned, and a Power Module that integrates on a single boardthe voltage and current measurement circuits, power devices, DClink (Direct Current) and capacitor bank. Finally, an exampleof implementation of a single-phase Dual Active Bridge (DAB)DC-DC converter is presented with its experimental results.